Competitive advantage of fruit and vegetable SMEs in Colombia: role of open innovation and entrepreneurial orientation - Echeverri-Romero, Rubén Darío; Silva-Castellanos, Tulio Ferney; Ruano-Arcos, Leidi Dayely; Sánchez-Álvarez, Jherónimo; Ordóñez-Tovar, Isabel Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This research studies the underlying effects of open innovation on the relationship between entrepreneurial orientation and competitive advantage. The hypotheses were tested using structural equations in PLS-SEM for the data collected in a Likert scale instrument, to a sample of 102 fruit and vegetable SMEs in Valle del Cauca, Colombia. The results show that entrepreneurial orientation positively influences open innovation; In turn, open innovation affects competitive advantage, thus proving the mediating role of open innovation. In other words, it is not enough for SME managers to be proactive, risky and innovative to achieve competitive advantage, they must also incorporate open innovation practices to achieve sustainable competitive advantage. This study contributes to the emerging literature on the underlying effects of open innovation, as well as its effects on competitive advantage.